Analysis of String Matching Application on Serial Number Using Boyer Moore Algorithm - Tarigan, Dede A.; Buaton, Adiyanto O.; Briyandana , Briyandana; Safitri, Erica R.; Rosnelly , Rika (Information Technology and Science (ITScience), 2024)
Nowadays, technology has become the most important pillar in business management. The rapid development of technology has a significant impact on various aspects of business, from operational efficiency to marketing strategies. Applications are very important in a company or agency. With an information system, companies and agencies can easily guarantee the quality of information that will be presented for decision-making. Now, much information can be easily obtained quickly, thanks to information technology. The speed and accuracy of information delivery is a challenge for all producers in running their business. Boyer-Moore algorithm is one of the algorithms that can be used in the Barcode Generator application to scan barcode product serial numbers. The Boyer-Moore algorithm method functions to find sequence numbers. The development process requires several stages of investigation in the form of data collection techniques, problem identification, application of the Boyer-Moore algorithm, implementation, and system testing. This iterative process makes the application of string matching with the Boyer-Moore algorithm technique into a very accurate application suitable for text search. This process is done by giving a pattern to the text. Therefore, the final result of string matching text search using the Boyer-Moore algorithm technique requires nine iterations. In the 9th iteration, the text and pattern conditions are matched or sequential. From the results of the manual computational search analysis work of applying the Boyer Moore string matching algorithm, several stages of the process are made, namely iterations 1 to 9, as a search step to determine string matches. In addition, patterns can be used with the number of shifts of patterns or text up to 13 times.